The Correspondences of the Phonemes [e̤.], [o.] and [ie], [uo] in the Unstressed Syllables of the Pašušvys Subdialect - Kazlauskaitė, Rūta (Kalbotyra, 2004)
An empirical, spectral and statistical analysis has proved that in the unstressed syllables of the Pašušvys subdialect (a northern West-Aukštaitian dialect) the front phonemes /e̤./, /ie/ together with the allophones [e. (æ.)]. [e (æ)] which belong to the low phonemes /a./, /a/ are realised by the same short vowel [e/ẹ] The back labial phonemes /o./, /uo/ and /u./, /u/ are realised by the more open or close short allophone of the [u] type.